Permutation based load balancing technique for long term evolution advanced heterogeneous networks - Mohammed Jaber Alam; Abdul Gafur; Syed Zahidur Rashid; Md. Golam Sadeque; Diponkor Kundu; Rosni Syed (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Traffic congestion has been one of the major performance limiting factors of heterogeneous networks (HetNets). There have been several load balancing schemes put up to solve this by balancing load among base stations (BSs), but they appear to be unfeasible due to the complexity required and other unsatisfactory performance aspects. Cell range extension (CRE) has been a promising technique to overcome this challenge. In this paper, a permutation based CRE technique is proposed to find the best possible formation of bias for BSs to achieve load balance among BSs. In comparison to the baseline scheme, results depict that the suggested method attains superior performance in terms of network load balancing and average throughput. The complexity of the suggested algorithm is considerably reduced in comparison to the proposed permutation based CRE method it is further modified from.